Shizofren odnos med politiko in gospodarstvom - spremljevalec tranzicije? - Svetličič, Marjan (Teorija in praksa, 2000)
Too frequently schizophrenic relationship is prevailing in transition between government and companies. In fighting for economic power, parties are interfering inappropriately. It is crucial that the government creates business-friendly climate - infrastructure. Political parties should not interfere in government - company's relations. The role of the government should be restricted to correcting market failures and visionary creating strategic long-term directions for the national economy. Ten commandments relating to the economy - politis relationship are elaborated in the text.
Keywords: Slovenia; Slovenija; ekonomska politika; vladna politika; political party; politične stranke; gospodarstvo; economy; tržno gospodarstvo; tranzicija